A Review on Metasurface: From Principle to Smart Metadevices - Hu, Jie; Bandyopadhyay, Sankhyabrata; Liu, Yu-hui; Shao, Li-yang (Frontiers in Physics, 2021)
Metamaterials are composed of periodic subwavelength metal/dielectric structures that resonantly couple to the electric and magnetic fields of the incident electromagnetic waves, exhibiting unprecedented properties which are most typical within the context of the electromagnetic domain. However, the practical application of metamaterials was found critical due to the high losses, strong dispersion associated with the resonant responses, and the difficulty in the fabrication of nanoscale 3D structures. The optical metasurface is termed as 2D metamaterials that inherent all of the properties of metamaterials and also provide a solution to the limitation of the conventional metamaterials. Over the past few years, metasurfaces have been employed for the design and fabrication of optical elements and systems with abilities that surpass the performance of conventional diffractive optical elements. Metasurfaces can be fabricated using standard lithography and nanoimprinting methods which is easier in terms of fabrication of its counterpart 3d metamaterials. In this review article, the progress of the research on metasurfaces is illustrated. Concepts of anomalous reflection and refraction, applications of metasurfaces with the Pancharatanm-Berry Phase, and Huygens metasurface are discussed. The development of soft metasurface opens up a new dimension of application zone in conformal or wearable photonics, the progress of soft metasurface also been discussed in this review. Meta-devices that are being developed with the principle of the shaping of wavefronts are elucidated in this review. Furthermore, it was established that properties of novel optical metasurface can be modulated by the change in mechanical, electrical, or optical stimuli which leads to the development of dynamic metasurface. Research thrust over the area of tunable metasurface has been reviewed in this article. Over the recent year, it has been found that optical fibers and metasurface are coagulated for the development of optical devices with the advantage of both domains. The metasurface with lab-on fiber-based devices is being discussed in this review paper. Finally, research trends, challenges, and future scope of the work are summarized in the conclusion part of the article.